The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1152/ajprenal.90399.2008
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone in the brain

Abstract: Pharmacological and physiological phenomena suggest that cells somewhere inside the central nervous system are responsive to aldosterone. Here, we present the fundamental physiological limitations for aldosterone action in the brain, including its limited blood-brain barrier penetration and its substantial competition from glucocorticoids. Recently, a small group of neurons with unusual sensitivity to circulating aldosterone were identified in the nucleus of the solitary tract. We review the discovery and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
151
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 199 publications
(310 reference statements)
2
151
0
Order By: Relevance
“…Aldosterone, another natriorexigenic hormone, is known to be detected by 11β-hydroxysteroid dehydrogenase type 2 (HSD2)-positive neurons in the nucleus of the solitary tract (NTS) and to induce salt appetite (Geerling and Loewy, 2009). …”
Section: Iii4 Discussionmentioning
confidence: 99%
“…Aldosterone, another natriorexigenic hormone, is known to be detected by 11β-hydroxysteroid dehydrogenase type 2 (HSD2)-positive neurons in the nucleus of the solitary tract (NTS) and to induce salt appetite (Geerling and Loewy, 2009). …”
Section: Iii4 Discussionmentioning
confidence: 99%
“…12 However, the enzymes for steroid biosynthesis are present in the central nervous system 41 and RVLM, 15 and aldosterone can be detected in the tissues of various brain regions in vitro 41 and in vivo. 42 In particular, it should be noted that Gomez-Sanchez et al reported that aldosterone was detectable in the whole brain of adrenalectomized rats, despite the fact that plasma aldosterone was undetectable.…”
Section: Discussionmentioning
confidence: 99%
“…11 Recent studies have reported the distribution of MRs or ENaCs in the choroid plexus, ependyma and neurons, such as those in the supraoptic nucleus, paraventricular nucleus and nucleus tractus solitarius. 12,13 In addition, the expression of MR mRNA has been reported in the brainstem, 14 including the rostral ventrolateral medulla (RVLM) and caudal ventrolateral medulla. 15,16 These findings suggest that MRs in the central nervous system, especially in neurons, regulate Na + influx via ENaCs, leading to hypertension and sympathoexcitation.…”
Section: Introductionmentioning
confidence: 99%
“…Both MR and GC receptors mediate rapid non-genomic effects via the binding of cortisol to cell membranes [86] . In the CNS, MRs bind very low levels of GCs in vivo [87,88] against the 100-1000-fold molar excess of GCs that circulate in the blood [85] .…”
Section: Glucocorticoid Receptorsmentioning
confidence: 99%
“…Both MR and GC receptors mediate rapid non-genomic effects via the binding of cortisol to cell membranes [86] . In the CNS, MRs bind very low levels of GCs in vivo [87,88] against the 100-1000-fold molar excess of GCs that circulate in the blood [85] .The acute effects of GCs on target cells in the HPA axis are predominantly mediated via their rapid action at their receptor sites. This action produces a rapid negative feedback response of the HPA axis that suppresses its own stress-induced hyperactivity.…”
mentioning
confidence: 99%